H(1)=-6 h(2)= 20 h(n)= h(n-2)+h(n-1) What is the value of h(3)?
1 answer:
9514 1404 393
Answer:
14
Step-by-step explanation:
Use the formula with n=3.
h(3) = h(3-2) +h(3-1)
h(3) = h(1) +h(2)
h(3) = -6 +20 . . . . . substitute the given values
h(3) = 14
You might be interested in
Answer:
third option
Step-by-step explanation:
Answer:
89
Step-by-step explanation:
21+13+19+36=89
Answer:
i think that this is the answer
Answer: I believe the correct answer is option D.
Answer:
0.014767
Step-by-step explanation: